Providing technical and algorithmical support to the predictable properties of honeycomb filler obtained by additive processes - Salenko, Oleksandr; Strutinsky, Vasil; Avramov, Konstantyn; Orel, Vadym; Dzhulii, Dmytro; Havrushkevych, Andrii; Kostenko, Anton (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the FDM process underlying the 3D printing of thin-walled honeycomb-type shells. A solution to the problem of manufacturing a honeycomb filler for a sandwich panel or a panel as a whole, including a curved one, is based on the built model of the process parametric and functional reliability. To this end, the printer dynamics, the behavior of a non-rigid workpiece, and the peculiarities of filament feeding during printing have been analyzed in detail. It has been shown that the predicted mechanical properties, in particular, [σ]x,y,z, are determined by the conditions of extrudate laying and the adhesive bonds formed between its elements, both in the laying plane and between layers, and depend directly on the laying density and on a number of dynamic and thermal phenomena occurring in the mating area. The layout density parameter ρ can be used as a factor in the strength characteristics of the finished article. The application of rational conditions for the movement of the print head, certain features of the contour traversal, the use of supporting elements, and the correct positioning of the part on the printer’s desktop allows for sufficiently reliable reproduction of cellular shell products with maximum strength. It has been proven that the accuracy of basic dimensions of the designed structures corresponds to accuracy quality 11...12 according to engineering standards, which is acceptable for a wide range of applications. The wall thickness of the cellular elements is determined by the filament laying modes, which includes such parameters as extrusion speed, contour traversal speed and acceleration, extrusion temperature, and stacking pitch, but is not less than 1.5 times the diameter of the extruder nozzle. Such geometric parameters provide reasonable strength and rigidity for articles at operation while minimizing the weight of the honeycomb. It has been established that cellular elements should be printed with the use of additional support means; at the same time, the latter do not exclude the occurrence of a certain number of defects whose evolution is not stable and whose presence must be taken into account when predicting the mechanical properties of the finished article